1987
DOI: 10.1038/bjc.1987.262
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone binding globulin and risk factors for breast cancer in a population of normal women who had never used exogenous sex hormones

Abstract: Summary Sex hormone binding globulin (SHBG) concentrations were measured by immunoradiometric assay in serum samples from 1,221 healthy female volunteers aged 34-79 who had never used oral contraceptives or hormone replacement therapy, had no history of thyroid disease or cancer, and had not used any drugs known to influence SHBG in the 14 days preceding blood sampling. There were 616 premenopausal and 605 naturally postmenopausal women. In both premenopausal and postmenopausal women, SHBG decreased with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 20 publications
(15 reference statements)
6
28
1
Order By: Relevance
“…A similar relationship was noted previously for SHBG (Moore et al, 1987), but the duration of storage before SHBG assays was relatively short. This phenomenon does not affect the case-control comparisons because cases and control subjects were matched for year of blood collection.…”
Section: Measurement Of Serum Hormone Concentrationssupporting
confidence: 84%
“…A similar relationship was noted previously for SHBG (Moore et al, 1987), but the duration of storage before SHBG assays was relatively short. This phenomenon does not affect the case-control comparisons because cases and control subjects were matched for year of blood collection.…”
Section: Measurement Of Serum Hormone Concentrationssupporting
confidence: 84%
“…A similar relationship had been noted previously for SHBG (Moore et al, 1987), but the duration of storage before SHBG assays was relatively short. The British Journal of Cancer (1997) Odds ratios for breast cancer in thirds of the distribution of hormone concentrations in the controls were calculated for matched case-control sets using conditional logistic regression, with the lowest concentration third as a reference.…”
Section: Measurement Of Serum Hormone Concentrationssupporting
confidence: 83%
“…Again, however, these changes could be accounted for by obesity as we have demonstrated in a previous study that obese women are more likely to have an early age of menarche and late age at menopause (Ingram et al, 1989). Moore et al (1987) similarly demonstrated that late menarche was associated with increased SHBG and adjusting for QI reduced the magnitude of the association; we have demonstrated here that adjusting for body mass reduced the assocation between age at menopause and oestradiol binding and SHBG. Little can be made of the other variables of risk and their associations with oestradiol and its binding.…”
mentioning
confidence: 71%